2015
DOI: 10.1055/s-0035-1565248
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Peripheral Nerve Interface for Prostheses Control: Electrode Comparison

Abstract: Epimysial patch electrodes outperform intramuscular hook electrodes during chronic skeletal muscle implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…9,18 In the beginning, there were no neuroma formations in laboratory animal studies based on this approach. [28][29][30] Woo et al 18 conducted a pilot clinical study on 16 amputees and demonstrated a decrease in neuroma and phantom pain.…”
Section: Discussionmentioning
confidence: 99%
“…9,18 In the beginning, there were no neuroma formations in laboratory animal studies based on this approach. [28][29][30] Woo et al 18 conducted a pilot clinical study on 16 amputees and demonstrated a decrease in neuroma and phantom pain.…”
Section: Discussionmentioning
confidence: 99%
“…This distinct feature of RPNI surgery to harness discrete motor and sensory signals through reinnervation of multiple individual RPNIs is advantageous when using it as an interface for advanced prosthetic limb rehabilitation. 38–47,86…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, it is a sieve made of silicon, ceramic or polymer with a large number of fine holes that is placed inside the transected nerve. The increase in growth rate of regeneration of individual or a group of fibers through those holes can activate selective stimulation and make it possible to record action potentials (Micera and Navarro, 2009 ; Sando et al, 2016 ) from individual axons or a small group. In principle, a high number of selective contacts can be achieved by reducing the size of the sieve along with an increased number of fine holes (Lago et al, 2007a ).…”
Section: Invasive Methods Of Sensory Feedbackmentioning
confidence: 99%